2016
DOI: 10.1007/s10008-016-3293-5
|View full text |Cite
|
Sign up to set email alerts
|

The application of activated carbon modified by ozone treatment for energy storage

Abstract: Activated carbon modified by ozone treatment was examined. The process was carried out in a glass reactor under a continuous flow of ozone through a bed of activated carbon for 15, 30, 60, 120, and 240 min. The modified and unmodified carbon materials were characterized by Raman spectroscopy and observed by scanning electron microscopy (SEM). Thermogravimetric analysis was used to estimate the presence of oxygen groups in the carbon structure. The surface area and pore size distribution were examined by nitrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 45 publications
2
35
0
Order By: Relevance
“…The sample subjected to the electric field shows a shift of the G-band. A similar result was observed by Lota et al, who exposed an activated carbon to ozone [54]. This trend may be explained by the loss of C bonded in rings and the formation of chains due to the incorporation of oxygen and nitrogen atoms, which is consistent with the previous FTIR and Bohem titration results.…”
Section: Raman Spectroscopysupporting
confidence: 91%
“…The sample subjected to the electric field shows a shift of the G-band. A similar result was observed by Lota et al, who exposed an activated carbon to ozone [54]. This trend may be explained by the loss of C bonded in rings and the formation of chains due to the incorporation of oxygen and nitrogen atoms, which is consistent with the previous FTIR and Bohem titration results.…”
Section: Raman Spectroscopysupporting
confidence: 91%
“…Materials 2020, 13, 400 10 of 18 [40]. D band and G band are also visible in Raman spectrum of all the study composites and they are indicated in Figure 5.…”
Section: Physical and Chemical Characterization Of Carbon Fiber-silicmentioning
confidence: 76%
“…The first one (D band) is related to the breathing modes of sp 2 atoms in rings and corresponds to the structural defects or edges in the carbon structure. The second one (G band) is associated with the bond stretching of all pairs of sp 2 atoms in both rings and chains [40]. D band and G band are also visible in Raman spectrum of all the study composites and they are indicated in Figure 5.…”
Section: Physical and Chemical Characterization Of Carbon Fiber-silicmentioning
confidence: 79%
“…The content of functional groups on the AC surface is mainly affected by the precursor, the activation process, and thermal and chemical treatment . In addition, the species and content of functional groups can be modified by physical, chemical, and biological modification processes , , .…”
Section: Introductionmentioning
confidence: 99%